Black phosphorous-based biomaterials for bone defect regeneration: a systematic review and meta-analysis - Jinfeng Huang; Ana Cláudia Santos; Quanchang Tan; Hao Bai; Xiaofan Hu; Narsimha Mamidi; Zixiang Wu (Journal of Nanobiotechnology, 2022)
Abstract Critical-sized bone defects are always difficult to treat, and they are associated with a significant burden of disease in clinical practice. In recent decades, due to the fast development of biomaterials and tissue engineering, many bioinspired materials have been developed to treat large bone defects. Due to the excellent osteoblastic ability of black phosphorous (BP), many BP-based biomaterials have been developed to treat bone defects. Therefore, there are abundant studies as well as a tremendous amount of research data. It is urgent to conduct evidence-based research to translate these research data and results into validated scientific evidence. Therefore, in our present study, a qualitative systematic review and a quantitative meta-analysis were performed. Eighteen studies were included in a systematic review, while twelve studies were included in the meta-analysis. Our results showed that the overall quality of experimental methods and reports of biomaterials studies was still low, which needs to be improved in future studies. Besides, we also proved the excellent osteoblastic ability of BP-based biomaterials. But we did not find a significant effect of near-infrared (NIR) laser in BP-based biomaterials for treating bone defects. However, the quality of the evidence presented by included studies was very low. Therefore, to accelerate the clinical translation of BP-based biomaterials, it is urgent to improve the quality of the study method and reporting in future animal studies. More evidence-based studies should be conducted to enhance the quality and clinical translation of BP-based biomaterials.